1990
DOI: 10.1136/bmj.300.6730.986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reactive pharmacy intervention on quality of hospital prescribing.

Abstract: Conclusions-Most reactive pharmacy interventions concerned prescribing errors with a limited potential for medical harm, but a small number of detected errors with a major potential for medical harm; cost savings were not appreciable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 17 publications
9
67
1
Order By: Relevance
“…The high percentage of interventions that were accepted by a physician showed that the vast majority were appropriate. The acceptance rate was similar to that reported in the USA, 17 and higher than a UK study, 18 where 83% of interventions made by a pharmacist were accepted, with the prescription altered in 75% of cases.…”
Section: Discussionsupporting
confidence: 68%
“…The high percentage of interventions that were accepted by a physician showed that the vast majority were appropriate. The acceptance rate was similar to that reported in the USA, 17 and higher than a UK study, 18 where 83% of interventions made by a pharmacist were accepted, with the prescription altered in 75% of cases.…”
Section: Discussionsupporting
confidence: 68%
“…Hence periodical auditing of drug utilization pattern is vital for promotion of rational use of drugs, for increasing the therapeutic efficacy and the cost effectiveness, for decreasing the adverse effects and to provide feedback to the prescribers 3 . It is important to realize that inappropriate use of drugs represent a potential hazard to the patients and an unnecessary expense 4 . Historically the pharmaceutical and medical profession has devoted considerable time and efforts to the development and rational utilization of safe and effective drugs for the treatment and prevention of illness.…”
Section: Introductionmentioning
confidence: 99%
“…Several e cient procedures for dealing with non-HDF requests have been postulated [32,33,34,35,36]. However, the availability of research evidence on HDF non-adherence is limited.…”
mentioning
confidence: 99%